1963
DOI: 10.1099/00221287-30-1-131
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Sites of Synthesis of Encephalomyocarditis Virus Components in Krebs-2 Ascites Tumour Cells

Abstract: SUMMARYAscites tumour cells were homogenized and fractionated at various times after infection with encephalomyocarditis virus in vitro. Infective ribonucleic acid (RNA) could be obtained from the nuclear fraction soon after infection and the amount of infective RNA recovered from this fraction increased until a maximum was reached a t about 44hr. From 4 h r . onwards the amount of infective RNA associated with the nuclear fraction fell while that from the mitochondrial fraction increased, reaching a maximum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

1964
1964
1972
1972

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 13 publications
1
2
1
Order By: Relevance
“…With these nucleus isolation techniques, it has been shown, in confirmation of earlier work, that NDV, like other RNA viruses (2,13), matures in the cytoplasm and PYV in the nuclei.…”
supporting
confidence: 76%
“…With these nucleus isolation techniques, it has been shown, in confirmation of earlier work, that NDV, like other RNA viruses (2,13), matures in the cytoplasm and PYV in the nuclei.…”
supporting
confidence: 76%
“…There was, however, a late increase in the infectivity of cytoplasmic SDS-extracted RNA. Hours after infection Ir&acellular location of phenol-emtracted RNA There was no long period of accumulation of infective phenol-extracted RNA in the nuclear fraction of L-cells infected by EMC virus, in contrast to our previous results with Krebs-2 ascites cells (Bellett & Burness, 1963); nevertheless, when the results of several experiments were compared it was found that the increase in infective RNA extracted from the nuclear fraction by phenol occurred consistently 30-60 min. before the increase in cytoplasmic infective RNA (Fig.…”
Section: Iintracellular Location Of Sds-extracted Rnacontrasting
confidence: 53%
“…Strain K2 of EMC virus (10) was grown in Krebs II ascites cells (11) and purified either by the procedure of Burness (12) or, more recently, by that of Kerr and Martin (13). RNA was extracted from purified virus by the method of Kerr et al (14), precipitated with ethanol, dialyzed against oocyte injection medium (2), and stored at -70°.…”
Section: Methodsmentioning
confidence: 99%